2010
DOI: 10.4314/bajopas.v3i1.58782
|View full text |Cite
|
Sign up to set email alerts
|

Dacterial agents of otitis media and their sensitivity to some antibiotics in Aminu kano teaching hospital, Kano state

Abstract: Fifty ear swab samples were examined from pediatric patients attending Aminu Kano Teaching Hospital, Kano. The samples were collected from ENT department, pediatric out patients department (PODP) and General out Patients Department (GOPD). The swabs were tested by culturing for bacterial pathogens, where 47 (94.0%) of the samples yielded growth. The most predominant isolate was Staphylococcus aureus, with a total occurrence of 26 (55.32%) followed by Proteus mirabilis, Pseudomonas aeruginosa, Klebsiella pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…was the leading causative fungal isolates 82.9% among 567 ear discharge swabs collected from patients diagnosed as otomycosis admitted to Department of Otolaryngology, Tongji Hospital, Tongji Medical Center, Wuhan, China. Overall, the identified MDR bacterial and resistant fungal strains in the present study are in accordance with other previous studies in Egypt and Africa [3,36,38,48,51]. These MDR strains are environmental organisms that are transmitted through water and soil [6] and opportunistic pathogens found in the human microbiome as Alc.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…was the leading causative fungal isolates 82.9% among 567 ear discharge swabs collected from patients diagnosed as otomycosis admitted to Department of Otolaryngology, Tongji Hospital, Tongji Medical Center, Wuhan, China. Overall, the identified MDR bacterial and resistant fungal strains in the present study are in accordance with other previous studies in Egypt and Africa [3,36,38,48,51]. These MDR strains are environmental organisms that are transmitted through water and soil [6] and opportunistic pathogens found in the human microbiome as Alc.…”
Section: Resultssupporting
confidence: 91%
“…In an earlier study carried out by Ganesh and Subramaniam [37], it was found that CIP and amikacin were the most effective drugs, followed by AX-clavulanate and ceftazidime for many organisms. However, another study [48] reported high resistance to ampicillin, clotrimazole, cefixime, and CIP, while, sensitivity to Augmentin (AX-clavulanate), OFX, AX, TE, C, and erythromycin was reported. Udden et al [38] observed higher sensitivity to AX, CTX, CIP, CN, TOB, TE, and C against 823 bacterial isolates obtained from ear discharge and nasopharyngeal samples in Ear, Nose and Throat Department at Hospital Josina Machel, Luanda, Angola.…”
Section: Resultsmentioning
confidence: 97%
“…The source of infection with gram negative enterobacteriaceae may not in necessarily come from the nasopharyngeal passage, it may come from the ear canal contamination with feces, and that due to the poor hygiene or the ignorance to the importance of the daily cleansing of the ear that the child must receive regularly (20).…”
Section: Discussionmentioning
confidence: 99%